The Relationship Between Emotional Intelligence and Leadership Styles: A Systematic Literature Review of Their Impact on Leadership Effectiveness - Herty Ramayanti Sinaga (LPPM Politeknik Pratama, 2025)
Emotional intelligence (EI) is an important psychological foundation in modern leadership practice. Leaders who have high EI tend to be able to understand and manage their own and others' emotions effectively, allowing for the implementation of a more adaptive and positive leadership style. Transformational leadership, for example, relies heavily on the leader's ability to show empathy, build intrinsic motivation, and provide individual attention to subordinates. EI strengthens these capacities and encourages leaders to create harmonious and inspiring working relationships. On the other hand, leaders who are low in EI tend to be authoritarian or use a rigid transactional leadership style, which has a negative impact on employee satisfaction and performance. Leadership effectiveness, in this context, is determined not only by the style used, but also by the emotional quality of the leader in executing the style. Therefore, the integration of EI and leadership style contributes directly to the achievement of organizational goals through increased individual performance, loyalty, and a productive work climate. Thus, the development of EI is a strategic need in today's leadership training and development.